Housing justice as a deprivation of capabilities: A conceptual model for public policies (Revista Direitos Humanos e Democracia, 2026)
Housing justice, understood as a concept opposed to homelessness, is often reduced to a view of adequate housing, neglecting the complexity and multidimensionality of this conception. Using the hypothetical-deductive method and a literature review, this article interprets homelessness from the perspective of Amartya Sen and Martha Nussbaum's Capabilities Approach. The central hypothesis is that homelessness constitutes a deprivation of capabilities that transcends physical deprivation, requiring a multidimensional reconceptualization. With a structured theoretical framework, the article proposes six dimensions that, together with the work on capabilities, form the basis of a conceptual model. This model explains what is understood by homelessness as capability deprivation, while situating housing concepts within a broader political-philosophical discourse on housing justice. It recognizes housing as a locus of well-being and capabilities as a valuable informational basis for evaluating public policy outcomes.
Keywords: Capability Approach; Home; Adequate housing; Capability deprivation; Amartya Sen